A day in the career of a social worker (MSW) - Siegel, Irene; Fardella, Daniel J.; Vocational Video, Inc.; Insight Media (Firm) ([New York] : Distributed by Insight Media, 2000)
Irene Siegel, a clinical social worker, describes what social workers do, sample job requirements from newspaper ads, the types of settings in which they work and the types of social work, and what a typical day is like for her. Her discussion with a client, Antoinette Paris, is shown. Teresa Simeone, MSW, is also interviewed. Includes the salary range, vocational advice, and a list of organizations to contact for more information about becoming a social worker.
DVD-R.
Host, Daniel J. Fardella ; featured social worker, Irene Siegel.
"Dan's original Get a life series"--Disc label.
Keywords: Social service -- United States; Social service -- Vocational guidance -- United States